Legal instruments in the spatial planning sector as a spatial utilization control tool - Tunjung Fitra Wijanarko; Mochamad Moro Asih (The International Journal of Politics and Sociology Research, 2023)
Spatial utilization control, as an integral part of spatial utilization process, is an important element which have its function to maintain the order of spatial utilization, in accordance to planning direction. In the spatial utilization control action, instruments as a mechanism tools is a requirement, specifically related to law. The two is (spatial utilization) permit and sanctions. Permit and sanctions are closely related to spatial utilization enforcement, as a final mechanism of prosecution of spatial planning violations. To imposing a sanctions to the violators of spatial planning, legal instrument of spatial planning is a vital instrument. Its key functions is to analyze and to imposing a legal actions to spatial planning violator